Heavy metal removal by bacterial isolates from the antarctic oceanic region - ANURADHA R MULIK; RAMA K BHADEKAR (International Journal of Pharma and Bio Sciences, 2017)
Cost effectiveness, in situ or ex situ treatment, complete degradation of the contaminants are some of the advantages of bioremediation which is a natural process and perceived positively in the treatment of hazardous pollutants. In view of this, fourteen bacterial isolates from oceanic region were screened for their heavy metal tolerance. Among them, four isolates viz. Kocuria sp BRI 36, Brevibacillus sp 37, Halomonas sp 38 and Oceanobacillus sp 39 with maximum tolerance for Cd2+, Cr3+, Ni2+ and Pb2+ were selected for further study. Their maximum tolerable concentration (MTC) values were in the range of 300-600 ppm with cell viability in the range of 47.1 to 6.6 %. Maximum survival was observed in case of BRI 39 in presence of Ni2+. Percentage of total metal removal in the range of 6 to 95.39 % was recorded using these isolates with i) 95.4 % removal of Cd2+ by BRI 36 ii) 86.7 % removal of Pb2+ by BRI 36 and iii) 88.2 % removal of Cd2+ by BRI 38 . Metal ion distribution studies indicated maximum intracellular accumulation of Cd2+ by BRI 36 (85 %) whereas Ni2+ was mainly depleted due to cell adsorption in case of BRI 38 (20.29 %). To summarize, Kocuria sp BRI 36 was observed to be the best candidate with significant potential for removal of Pb2+ and Cd2+.